Say Goodbye to the ‘Great Resignation’ Phenomenon: Why HRM Interventions Must Start Understanding the Psychological Dynamics that Drive Employees’ Career Decision-Making - Izzun Naila Fithriyah; Alldila Nadhira Ayu Setyaning (Cita Konsultindo Research Center, 2024)
The Great Resignation underscores the imperative for integrating more strategic Human Resource Management (HRM) interventions to effectively address employees' evolving aspirations following the COVID-19 pandemic, which significantly contribute to the complexity of their Career Decision-Making (CDM). This study aims to offer a new perspective on conceptualizing the potential mediating and moderating factors influencing employees’ CDM, while emphasizing the pressing urgency and relevance of HRM interventions. Utilizing a quantitative approach, data were collected from a diverse sample of 217 employees representing various industries, integrating both SPSS and PLS-SEM for data analysis. The findings of this study reveal several key valuable insights. Firstly, it was found that high Actual-Ideal Self-Discrepancy (AISD) significantly influences both the complexity of employees' CDM and Future Time Perspective (FTP). Specifically, high AISD is associated with increased complexity in CDM and a higher FTP. Furthermore, high FTP was identified as reducing CDM complexity, serving as a mediator in the relationship between high AISD and low complexity of CDM. However, it was also observed that high Willingness to Compromise (WTC) does not moderate the significant relationship between high AISD and high complexity of CDM. These findings highlight the importance of understanding the psychological dynamics that contribute to the complexity of employees' CDM. Organizations can use this knowledge to develop personalized interventions to mitigate turnover intentions and improve employee retention in the post-pandemic era.